Maynard weston dow (1929–2011) and “Geographers on film” - Martin, Geoffrey J (Annals of The Association of American Geographers, 2013)
Keywords: art; dept.egm

Lights, camera, action! Developing a methodology to document mainstream films’ portrayal of nature of science and scientific inquiry - Koehler, Catherine M; Bloom, Mark; Binns, Ian C (The Electronic Journal of Science Education, 2013)
Keywords: dept.egm; ⛔ No DOI found

Forest cover change in the northeastern U.S.: A spatial assessment in the context of an environmental kuznets curve - Bentley, George C; Cromley, Robert G; Hanink, Dean M; Heidkamp, C Patrick (International Journal of Applied Geospatial Research, 2013)
An analysis of the association of forest cover, treated as an environmental good, and income at the county scale in the Northeastern United States was conducted for 2006. Global analysis using a spatial error regression model indicates an environmental Kuznets curve (EKC) type of relationship, with total forest cover, percent forest cover, and forest cover per capita is better associated with per capita income and is better specified as a polynomial rather than in linear terms. Local analysis, using geographically weighted regression, indicates that sub-regional effects are pronounced, and that conformity to an EKC varies spatially and by forest cover measure. The findings should be interpreted strictly within their context of a cross-sectional analysis and within certain statistical limitations, primarily engendered by multicollinearity of the explanatory variables in the regression models. Copyright © 2013, IGI Global.
Keywords: Environmental Kuznets Curve; Forest Cover; Geographically Weighted Regression; Northeastern United States; Spatial Error Regression Model; dept.egm

Tax lien sales as local neoliberal governance strategy: The case of Waterbury, Connecticut - Botein, Hilary; Heidkamp, C Patrick (Local Economy, 2013)
This article examines bulk sales of municipal property tax liens in the formerly industrial city of Waterbury, Connecticut, USA, in the 1990s, in order to explore the limits and contradictions of neoliberal local governance strategies. In the USA, cities and states create property tax liens by reducing delinquent real estate taxes to a judgment that creates a legal claim against the property at issue. We argue that Waterbury's efforts to resolve its fiscal stress by enhancing short-term revenues ultimately further constrained its revenue base, the tax lien sales reflected a spatial selectivity that created barriers to revitalization when neither the city nor tax lien purchasers had incentives to foreclose on distressed properties in struggling neighborhoods, and the tax lien sales' failure to resolve the city's budget crisis set in motion new efforts at tax base enhancement through real estate-led development in the central business district that also were unsuccessful. © The Author(s) 2013 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Keywords: dept.egm; housing; local government; neighbourhood decline; neoliberalism; real estate taxes; tax liens; urban governance